Pewarnaan Sisi r-Dinamis pada Graf Khusus dan Graf Operasi Sakel - Viqedina Rizky Noviyanti; Kusbudiono Kusbudiono; Ika Hesti Agustin; Dafik Dafik (jcgant, 2021)
Let G=(V(G),E(G)) be a nontrivial connected graph. The edge coloring is defined as c:E(G) → {1,2,...,k}, k N, with the condition that no adjacent edges have the same color. k-color r-dynamic is an edge coloring of k-colors such that each edge in neighboring E(G) is at least min {r,d( u)+d(v)-2} has a different color. The dynamic r-edge coloring is defined as a mapping of c from E(G) such that |c(N(uv))| = min{r,d(u)+d(v)- 2}, where N(uv) is the neighbor of uv and c(N(uv)) is the color used by the neighboring side of uv. The minimum value of k so that the graph G satisfies the k-coloring r-dynamic edges is called the dynamic r-edge chromatic number. 1-dynamic chromatic number is denoted by λ(G), 2-dynamic chromatic number is denoted by λ_d(G) and for dynamic r-chromatic number is denoted by λ_r(G). The graphs that used in this study are graph TL_n, TCL_n and the switch operation graph shack(H_2,2,v,n).